Efektivitas Penyelenggaraan Pelayanan Publik di Pemerintahan Nagari Salido Kabupaten Pesisir Selatan - Melvi Chania; Hasbullah Malau (Lembaga Yasin AlSys, 2026)
The delivery of public services at the nagari level requires adequate organizational effectiveness, but studies that specifically discuss the effectiveness of nagari government services under conditions of limited facilities remain limited. This study aims to analyze the effectiveness of services in the Salido Nagari Government based on the aspects of goal achievement, integration, and adaptation. This study used a qualitative approach with a descriptive case study design, involving 12 informants selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using the Miles and Huberman interactive model. The results show that the aspects of goal achievement and integration have functioned fairly well, but the aspect of adaptation is still constrained by limited waiting-room space, internet networks, the shared use of the office with the KAN Building, and service dependence on the presence of certain officials. The conclusion of this study emphasizes that the provision of physical facilities and the strengthening of bureaucratic flexibility are important factors in improving the effectiveness of public services at the nagari level. These findings contribute to the development of Steers’ theory of organizational effectiveness and broaden understanding of public service management in nagari government. The implications of this study include the need to prepare written SOPs, add physical office facilities, digitize services, and develop further studies on the application of electronic signatures in nagari government.